2017
DOI: 10.1080/17290376.2017.1405838
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors predicting risky sexual behaviour among long distance truck drivers in Lagos, Nigeria

Abstract: Long distance truck drivers (LDTDs) have been identified as one of the groups at higher risk for human immunodeficiency virus (HIV) infection. Understanding how certain social and psychological variables that have a strong theoretical basis contribute to sexual risk behaviour will guide in the implementation process of HIV risk-reduction intervention in the trucking population. In line with the conceptualisation of Information, Motivation and Behavioural skills model, we examined the extent that HIV knowledge,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…For instance, our findings were partly with Amare, et al [7] and Berhan and Berhan [15] who in their systematic review and meta-analysis of predictors of risky sexual behaviour discovered that not all students of tertiary institutions engaged in unsafe sex out of their self-will but sometimes due to what they stood to derive from such practices or as results of poor understanding of the consequences of their risky sexual lifestyles. Also, our findings collaborated Chawla and Sarkar [27] and Lawal and Olley [31] who buttressed on the established direct and significant link between substance abuse, psychosocial factors and risky sexual behaviour lifestyles. This finding was a confirmation of our findings where our respondents admitted that had unprotected sex because they were drugged by their sexual partner(s).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…For instance, our findings were partly with Amare, et al [7] and Berhan and Berhan [15] who in their systematic review and meta-analysis of predictors of risky sexual behaviour discovered that not all students of tertiary institutions engaged in unsafe sex out of their self-will but sometimes due to what they stood to derive from such practices or as results of poor understanding of the consequences of their risky sexual lifestyles. Also, our findings collaborated Chawla and Sarkar [27] and Lawal and Olley [31] who buttressed on the established direct and significant link between substance abuse, psychosocial factors and risky sexual behaviour lifestyles. This finding was a confirmation of our findings where our respondents admitted that had unprotected sex because they were drugged by their sexual partner(s).…”
Section: Discussionsupporting
confidence: 80%
“…According to Awofala and Ogundele [19] and Lawal and Olley [31] it is obvious that a significant number of people living with HIV in Nigeria were not aware of their infection status; this has been generally linked to the poor level of the utilisation of voluntary counseling testing centres for HIV/AIDS in the country. On the other hand, there are gender disparities in the prevalence of HIV among young adults between ages 15-24 years in Nigeria.…”
mentioning
confidence: 99%
“…Regarding the relationship between sexual knowledge and behaviour, another study indicated that poor SRH knowledge of male youths increased the risk of female partners’ unintended pregnancy in China [ 27 ]. Regarding the relationship between sexual attitude and behaviour, a study concluded that psychological and social factors could jointly reduce sexual risk behaviours [ 28 ]. Furthermore, several psychosocial predictors of high-risk sexual behaviour were identified [ 29 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, personal factors are difficult to assess since they are influenced by individual lived experiences, biological, psychological and social variables (Wagenaar et al, 2018). Participants recognized the relationship between factors and their biological, psychological, and social consequences (Lawal & Olley, 2017). However, the key aspect that emerged from this study is the explicit explanation of stigma and taboo towards these behaviours, tending to blame and marginalize the people who suffer from it (Mudhovozi, 2011).…”
Section: Discussionmentioning
confidence: 87%